Liquid Crystalline Self‐Assembly with Accelerated Kinetics and Higher Structural Orderliness in Centrifugal Acceleration Fields Beyond 7251 Times Gravity of Earth - Lingyan Xu; Hongbo Zhao; Pei‐Xi Wang (Advanced Science)
Abstract Gravity of the Earth (g) drives the macroscopic differentiation of multiple phases with different volumetric mass densities in many chemical and physical processes. Herein, liquid crystalline phase separation of colloidal dispersions of rod‐shaped cellulose nanoparticles in centrifugal acceleration fields up to 71 061 meters per second squared (7251 g) is studied. Through non‐ionic in situ free‐radical polymerization initiated by time‐controllable oxidation–reduction reactions between tert‐butyl hydroperoxide (oxidants) and thiourea (thiocarbamide, reductants) at room temperature (298 kelvins), ordered soft microstructures formed by entropy‐driven self‐assembly are immobilized within crosslinked polyacrylamide matrixes at various evolution stages (e.g., after 10, 30, or 60 min) in centrifuge tubes. Based on cross‐sectional polarized optical and scanning electron microscopy, strong centrifugal acceleration fields accelerated the movement velocity of discrete liquid crystalline tactoidal microphases, the coalescence of tactoids into continuous chiral nematic structures, as well as the translational and rotational relaxation rates of mesogenic nanorods at kinetically arrested states in high‐viscosity concentrated colloidal liquid crystals, leading to the elimination of topological defects and improvements in structural orderliness. Since acceleration is indistinguishable from a homogeneous gravitational field according to Einstein's principle of equivalence in general relativity, these results might help to predict self‐assembling behaviors near compact astrophysical objects such as neutron stars.